2019
DOI: 10.1371/journal.pone.0218269
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of neuroblastoma cell response to treatment with natural or synthetic retinoids using selected protein biomarkers

Abstract: Although the administration of retinoids represents an important part of treatment for children suffering from high-risk neuroblastomas, approximately 50% of these patients do not respond to this therapy or develop resistance to retinoids during treatment. Our study focused on the comparative analysis of the expression of five genes and corresponding proteins (DDX39A, HMGA1, HMGA2, HOXC9 and PBX1) that have recently been discussed as possible predictive biomarkers of clinical response to retinoid differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Notably, the phase III treatment study of pediatric neuroblastoma using 13- cis -RA differentiating therapy showed that high-dose pulse therapy given following completion of intensive chemoradiotherapy significantly improved event-free survival in high-risk subtypes of the disease ( Reynolds et al, 2003 ). While the efficacy of retinoid therapy for neuroblastoma is clear, approximately 50% of patients fail to respond to treatment or become resistant during the course of therapy ( Dobrotkova et al, 2019 ).…”
Section: Early Embryogenic Pathways and Morphogensmentioning
confidence: 99%
“…Notably, the phase III treatment study of pediatric neuroblastoma using 13- cis -RA differentiating therapy showed that high-dose pulse therapy given following completion of intensive chemoradiotherapy significantly improved event-free survival in high-risk subtypes of the disease ( Reynolds et al, 2003 ). While the efficacy of retinoid therapy for neuroblastoma is clear, approximately 50% of patients fail to respond to treatment or become resistant during the course of therapy ( Dobrotkova et al, 2019 ).…”
Section: Early Embryogenic Pathways and Morphogensmentioning
confidence: 99%
“…Because it is very difficult to collect a large set of paired NBL samples before and after treatment with retinoids, this study cannot answer the question about the usefulness of these markers for predicting the response of patients to retinoids. Nevertheless, our already published study on this topic using a set of primary NBL cell lines confirmed the association of low levels of PBX1 with the sensitivity to retinoids (15).…”
Section: Discussionmentioning
confidence: 53%
“…Representative sections from archival FFPE tumor samples were selected by one experienced pathologist (MJ) and processed for IHC as described previously in detail (15). All antibodies used in this study are specified in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…HMGA1 has been described as N-Myc transcriptional target ( 57 ) and linked to resistance to apoptosis, proliferation induction, and angiogenesis, while it is implicated in the mechanism of resistance to retinoic acid in NB ( 58 60 ). We found in the previous section that HMGA1 is a regulon in the cluster 1 associated with poor prognosis in both the NB cohorts, regulated different genes in the MYCN immune signature and highly expressed in MNA NB patients ( Figure S15A ).…”
Section: Resultsmentioning
confidence: 99%